Technological infrastructure and financial resource availability in enhancing public services and government performance: The role of digital innovation adoption in Indonesia - Ratih Purnamasari; Agus Ismaya Hasanudin; Rudi Zulfikar; Helmi Yazid (Social Sciences and Humanities Open)
This quantitative study explores the relationships between technological infrastructure, financial resource availability, digital innovation adoption, public service enhancement, and government performance in Indonesia. It finds that technological infrastructure and financial resource availability significantly influence the adoption of digital innovation, subsequently improving public service quality and government performance. It underscores the crucial role of robust technological infrastructure in facilitating digital innovation adoption, challenging simplistic assumptions about the direct mediating role of digital innovation adoption in improving public service and government performance. Instead, it suggests a more intricate, context-specific relationship that warrants further exploration. Practically, the study highlights the need for organizations and governments to invest in technological infrastructure and allocate financial resources prudently and strategically. Comprehensive strategies are essential, including infrastructure development, financial planning, and effective digital innovation implementation. Rigorous evaluation and monitoring of initiatives are recommended to ensure desired public service and government performance outcomes. However, the research has limitations, such as contextual specificity, reliance on quantitative data, and temporal constraints. Future research should incorporate qualitative methods, delve deeper into underlying mechanisms, and include diverse contexts. Longitudinal studies tracking variable evolution and examining the impact of emerging technologies are also suggested. Comparative analyses between regions with varying technological development and resource allocation can offer valuable insights. In summary, this study contributes to understanding the intricate relationships between technological infrastructure, financial resources, digital innovation adoption, public service improvement, and government performance, offering guidance for policymaking and implementation in an increasingly digital world.